From IL-17 to IFN-γ in inflammatory skin disorders: Is transdifferentiation a potential treatment target? - Belpaire, Arno; van Geel, Nanja; Speeckaert, Reinhart (Frontiers in Immunology, 2022)
Targeted inhibition of effector cytokines such as interleukin 17 (IL-17) for psoriasis and IL-13 for atopic dermatitis offers impressive efficacy with a favorable side effect profile. In contrast, downregulation of interferon gamma (IFN-γ) for T helper (Th) 1 dominant skin disorders may lead to more adverse events, given its crucial role in antiviral and antitumoral defense. Modulating Th17 and Th2 cell differentiation can be done by blocking IL-23 and IL-4, respectively, whereas anti-IL-12 antibodies have a less dramatic effect on Th1 lymphocyte development. The targeted treatment of IFN-γ-driven disorders remains therefore challenging. Additionally, recent data indicate that also other immune cells such as IFNγ+IL-17+ (Th17.1) and IFN-γ+IL-17- (exTh17) lymphocytes contribute to Th1-mediated autoimmunity. This is due to the stem-cell like properties of Th17 lymphocytes providing the capacity to produce IFN-γ. Remarkably, these exTh17 lymphocytes are resistant to conventional therapies such as corticosteroids and other inflammation dampening mechanisms (e.g., regulatory T cells). ExTh17 lymphocytes may explain the lack of response of autoimmune diseases to conventional treatments. In this review, we summarize the current evidence regarding Th17 plasticity in skin disorders. This is not only important to shed more light on the pathogenesis, but may also support the development of new treatment strategies.